IDENTIFIKASI KEBERADAAN SISTEM PANAS BUMI MENGGUNAKAN DATA MAGNETOTELURIK DI DAERAH PROSPEK PANAS BUMI BUKIT KILI-GUNUNG TALANG SUMATERA BARAT - , MARTHA DWI MARDYANCILATIA, Drs. Imam Suyanto, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Bukit Kili-Gunung Talang is one of the prospective geothermal areas in West Sumatra. The area administratively lies at Solok Regency. The geothermal system in that location is supposed to have connection with Mt. Talang that remains an active volcano. The area is also crossed by the major Sumatran Fault. Geothermal manifestation is found around of fault that consist of steaming ground and hot spring. In this experiment is used 13 primary MT sounding that spread in a line about 18 km. The line lies in parallel with the major Sumatran Fault and crosses through some hot springs, with direction N 1500E. The raw time series data are collected from sounding, then they are converted to apparent resistivity curve. Then the curve is corrected using smoothing ,static shifting and running inversion to make 2D model. 2D modelling of magnetotelluric (MT) method is used to identify the existence of geothermal system 2D model result show the low resistivity zone (<20 ohmmeter) which indicates altered rocks presence as cap rock of the geothermal system in depth about 500-1500 meter under sea level. The top recervoir appears in depth about 2000-2500 meter under sea level.